A 380-gene meta-signature of active tuberculosis compared with healthy controls. Issue 6 (13th April 2016) - Blankley, Simon; Graham, Christine M.; Levin, Joe; Turner, Jacob; Berry, Matthew P.R.; Bloom, Chloe I.; Xu, Zhaohui; Pascual, Virgina; Banchereau, Jacques; Chaussabel, Damien; Breen, Ronan; Santis, George; et al.
Mycobacterium tuberculosis is estimated to have infected one third of the world's population and continues to be a significant cause of mortality and morbidity [1]. There is a need for new and improved diagnostics or treatment-monitoring tools and blood-based mRNA diagnostics are a potential solution [2]. Gene expression microarray analysis of human blood has been widely used to profile the host transcriptional response in active tuberculosis (TB) to identify potential biomarkers and better understand the host immune response [2]. So far, there has been a relative lack of concordance in the actual genes being identified from the published studies [2, 3], although there has been agreement in some of the pathways identified. Interferon (IFN) signalling has been identified as a dominant signature in many of the individual studies [2, 4]; however, when significant gene lists were combined from eight publicly available TB datasets, TREM1 (triggering receptor expressed on myeloid cells 1) signalling became the most significant pathway [5]. Modular and meta-profiling identify a common transcriptional response of patients with TB versus healthy controls http://ow.ly/YvEP7